2012
DOI: 10.4081/ejh.2012.e29
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan and collagen expression during human air conducting system development

Abstract: The lung is formed from a bud that grows and divides in a dichotomous way. A bud is a new growth center which is determined by epithelial-mesenchymal interactions where proteins of the extracellular matrix (ECM) might be involved. To understand this protein participation during human lung development, we examined the expression and distribution of proteoglycans in relation to the different types of collagens during the period in which the air conducting system is installed. Using light microscopy and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…Among the approximately 800 candidate genes, FN 1 was one of the high-scoring candidates. FN 1 is an ECM component, and the ECM is critical for lung development [7,11]. FN 1 plays a major role in fundamental biological processes such as cell adhesion and migration, maintenance of normal cell morphology, cytoskeletal organization, and cell differentiation [12].…”
Section: Resultsmentioning
confidence: 99%
“…Among the approximately 800 candidate genes, FN 1 was one of the high-scoring candidates. FN 1 is an ECM component, and the ECM is critical for lung development [7,11]. FN 1 plays a major role in fundamental biological processes such as cell adhesion and migration, maintenance of normal cell morphology, cytoskeletal organization, and cell differentiation [12].…”
Section: Resultsmentioning
confidence: 99%
“…The recent observation of the expression of collagens (I, III, VI) and biglycan, and its relation with blood vessel development during the human pseudoglandular period, has raised new questions regarding the mechanism involved in vascular network formation (Godoy‐Guzmán et al ). It has been shown that the vascular endothelial growth factor (VEGF) plays a significant role in vasculogenesis and angiogenesis, regulating vascular endothelial cell proliferation and differentiation (Neufeld et al ; Ferrara et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical analysis of lung tissue was performed according to Godoy‐Guzmán et al (). Briefly, sections were treated with 3% (v/v) H 2 O 2 in phosphate‐buffered saline (PBS) for 30 min to block endogenous peroxidase.…”
Section: Methodsmentioning
confidence: 99%
“…Standard protocols of immunohistochemistry (IHC) (Garcia‐Martinez, Campos, & Godoy‐Guzman, ; Godoy‐Guzman, San Martin, & Pereda, ) and confocal immunofluorescence (Itoh, Itoh, Tassoni, & Ren, ; Sun et al, ) were performed as described earlier with minor modifications. For both methods, tissue sections of 5 μm thick were deparaffinized in xylene and rehydrated through graded sets of ethyl alcohol.…”
Section: Methodsmentioning
confidence: 99%